The claim of identity as a form of black empowerment: Policy of actions in Brazil - Cavalcante , Jéssica Painkow Rosa; Macêdo , Maurides; Luz, Katariny Laboré Barbosa da (Seven Editora, 2023)
This article aims to show that the experience of slavery left deep traces in the daily life of the black population in Brazil. Analyzing higher education policies for the admission of black people to Federal Public Universities, we highlight the need for these to go beyond the recognition of black identities as instruments of empowerment of this social group, from a multicultural perspective. It is necessary to deconstruct ethnocentric and eurocentric narratives from a critical intercultural perspective. DOI:https://doi.org/10.56238/interdiinovationscrese-005